2019
DOI: 10.1039/c9ce00185a
|View full text |Cite
|
Sign up to set email alerts
|

Conformational variation of ligands in mercury halide complexes; high and low Z′ structures

Abstract: Small changes in the ligand resulted in a conformational variation of LPy to LPz which led to high and low Z′ structures in the corresponding metal complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…According to the results of rmsd, molecules in asymmetric unit are divided into four categories: (I) rmsd ≤ 0.1 for molecular shake, (II) 0.1 < rmsd ≤ 0.225 for partial conformational adjustment, (III) 0.225 < rmsd ≤ 0.375 for essential conformational adjustment, and (IV) 0.375 > rmsd for conformational change. 7 The rmsd for I , II , and III was calculated as 0.203, 0.135, and 0.088, respectively. Therefore, it is expected that I and II , belong to class II (partial conformational adjustment) and III belongs to class I (molecular shake).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of rmsd, molecules in asymmetric unit are divided into four categories: (I) rmsd ≤ 0.1 for molecular shake, (II) 0.1 < rmsd ≤ 0.225 for partial conformational adjustment, (III) 0.225 < rmsd ≤ 0.375 for essential conformational adjustment, and (IV) 0.375 > rmsd for conformational change. 7 The rmsd for I , II , and III was calculated as 0.203, 0.135, and 0.088, respectively. Therefore, it is expected that I and II , belong to class II (partial conformational adjustment) and III belongs to class I (molecular shake).…”
Section: Resultsmentioning
confidence: 99%
“…3 Several factors have been investigated as the possible reasons for the occurrence of packing problems in the structures: (a) synthon frustration 4 (b) awkwardness in molecular geometry 5 (c) the existence of multiple functional groups on the molecule which lead to strong directional interactions and competition among them during nucleation process 6 (d) conformational variability. 7 It is shown that the propensity for high Z ′ compounds can be enhanced via strong hydrogen bond motifs and other interactions in packing, as well. 8 The high Z ′ in compounds can be ascribed to hydrogen bond interactions between the symmetry independent (SI) molecules which are effective in stabilizing high Z ′ polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…As fundamental sciences merge to create privileged interdisciplinary ones, integration of pharmaceutical cocrystals with wide range of disciplines have been extensively progressed during the last years. A cocrystal is defined as a composition of two or more stoichiometric molecular/ionic entities in a homogeneous singular crystalline phase. , Cocrystal engineering utilizes the understanding of intermolecular interactions in the design of cocrystals with desired physicochemical properties and biological activities. In 2018, European Medical Agency (EMA) and US-FDA announced a general guideline for cocrystals as a group of new molecular solids. The crystal structure of cocrystals should be characterized by different spectroscopy techniques and dissociated before reaching the active pharmacological site .…”
Section: Introductionmentioning
confidence: 99%